Investigation on Solid Waste Management in Developing Countries - Adhikari, Ram Chandra (Journal of Research and Development, 2022)
Solid waste is global problem relating to environment, society and economics. Waste management is challenging issue as the quantity has been increasing with increase of population, urbanization and economic status. Some dozens of printed and online published books, journals, dissertations, website of agencies etc. were reviewed and by making outline and following guideline this article was prepared. It is found that the waste production varies from 0.25Kg to 1.38 Kg per capita per day in developing countries. In south South American countries it was recorded 1.07 Kg/capita/day, in Asian countries 0.4 to 1.62Kg/capita/day and in African region it was found 0.49 Kg/capita/day of waste production. The waste contains mostly biodegradable (50% to 80%). The collection system was very poor and from rural area only 10% to 20% waste and in urban area 44% to 90% of total produced waste was carried to collecting and management system. The common waste management’s adopted in developing countries were open dumping, landfill site, composting, incineration and open burning etc. From 18% to 92% of waste were found to dumping. In east pacific region 46% and in American countries 68.5% of total waste was carried to landfill site. The use of incinerator is scarcely found. Only in few countries well managed composting plants could be observed. Some landfill sites and incinerating plant shave generated electricity, biogas, brickets etc. Some pointed research gaps in this field are waste management and biodiversity, medicinal and hazardous waste management, vermicomposting etc. It can be recommended that for the waste management public awareness, participation of locals, application of reduction, reuse and recycling concept, waste management inside house premise, modernization and scientific management of solid wastes. Further researches are needed in different aspects of waste and management for the complete solution.